Attachment to family members and romantic partners with regard to completeness of family structure and the quality of parental relationship - Jelić, Margareta; Kamenov, Željka; Delač Horvatinčić, Ivana; Ivanković, Palmira (2008)
The aim of this research was to examine the differences in attachment to family members and romantic partners among individuals whose parents had divorced as opposed to those whose parents had high quality marriages and those whose parents had low quality marriages. 529 participants, students from various faculties of the University of Zagreb, were included in the research. 52.2% of them were female and 47.8% of them were male. The average age was M=21.6, SD=1.95. Data about family structure and the quality of parental relationship were obtained. Attachment to family members and attachment to romantic partners were assessed with comparable measures and results were computed separately for each dimension of both types of relations. Results showed significant sex differences only on Avoidance dimension in relationship with parents, but no gender differences were found on the Anxiety dimension, and no significant sex differences were found on dimensions of attachment to romantic partners. As far as effects of family structure and quality of parental relationship are concerned, significant differences emerged on Avoidance in attachment to family and on Anxiety in attachment to romantic partners due to low quality of parental relationship. No significant interactions of sex and family structure were found. Specifically, individuals whose parents had low marital quality while they were teenagers appear to be more avoidant towards their parents and more anxious in their romantic relationships in comparison with individuals in two other groups. These findings contribute to a new direction in research of consequences of divorce on children, which postulates parental marital discord accompanied by inadequate parental interaction and maladaptive communication strategies, and not merely divorce, to be the key factor detrimental to psychological functioning, well-being and social adjustment of children.
Projekt MZOS
Projekt MZOS
ENG